Innominate artery pathology in the setting of aortic arch surgery: incidences, surgical considerations and operative outcomes. (6th August 2018) - Urbanski, Paul P; Irimie, Vadim; Lenos, Aristidis; Bougioukakis, Petros; Atieh, Alaa; Lehmkuhl, Lukas
Abstract: OBJECTIVES: The aim of the study was to evaluate the incidences of innominate artery (IA) involvement in aortic arch pathology necessitating surgery, the surgical strategies and the operative results. METHODS: Among the 366 patients who underwent total/subtotal arch replacement because of non-acutely dissected aortic pathology between 2004 and June 2017, there were 46 (12.6%) patients (29 males; mean age 69 ± 10, range 35–84 years) with IA involvement. Pathologies necessitating replacement of the IA were chronic aneurysm including progression of chronic dissection, severe atherosclerosis with or without an aneurysmatic dilatation, and inflammatory vasculitis in 34, 11 and 1 patient, respectively. All data were collected prospectively, and intention-to-treat analysis was performed. RESULTS: All patients underwent total/subtotal aortic arch replacement using unilateral cerebral perfusion (mean duration 44.6 ± 15.7 min) under mild hypothermia (30.6 ± .4°C). In addition to arch and IA replacement, repair of one or two further supra-aortic arteries was performed in 20 and 23 patients, respectively. One patient underwent complete thoracic aorta replacement via clamshell thoracotomy. The aortic valve, which was the most frequent object of concomitant surgery, was replaced in 18 (including 3 valve composite-grafts) and repaired in 20 (18 valve-sparing root repairs) patients. Early (30-day and/or in-hospital) mortality was 0. The rate of permanent neurological deficit was 2.2% (1 patient with a huge, partially thrombosed arch and innominate aneurysm). Transient neurological dysfunctions such as agitation were observed in 6 patients. CONCLUSIONS: Involvement of the IA in aortic arch surgery is not infrequent, and its concomitant replacement using well-considered cannulation, perfusion and surgical strategy offers excellent operative outcomes.